2010
DOI: 10.1093/cid/ciq038
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Pandemic (H1N1) 2009 Influenza to Healthcare Personnel in the United States

Abstract: After identification of pandemic 2009 influenza (pH1N1) in the United States, the Centers for Disease Control and Prevention (CDC) worked with state and local health officials to characterize infections among healthcare personnel (HCP). Detailed information, including likely routes of exposure, was reported for 70 HCP from 22 states. Thirty-five cases (50%) were classified as being infected in healthcare settings, 18 cases (26%) were considered to have been infected in community settings, and no definitive sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
35
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 12 publications
1
35
0
Order By: Relevance
“…5,8,11,12,29 Recent studies suggest that during the 2009 influenza A (H1N1) pandemic, the virus was transmitted to health care workers most often through exposure resulting from inadequate PPE. [30][31][32] Concern for family safety is a widely recognized predictor of willingness to work during disasters, 11,16,25,28,[30][31][32][33] and we found it to be a powerful influence in this study. Willingness to work decreased if respondents lacked a personal family pandemic flu plan, if they weren't confident that their employer would ensure their family's safety while they cared for patients with pandemic flu, and even if vaccine and antiviral medication were provided for both nurse and family.…”
Section: Discussionsupporting
confidence: 52%
“…5,8,11,12,29 Recent studies suggest that during the 2009 influenza A (H1N1) pandemic, the virus was transmitted to health care workers most often through exposure resulting from inadequate PPE. [30][31][32] Concern for family safety is a widely recognized predictor of willingness to work during disasters, 11,16,25,28,[30][31][32][33] and we found it to be a powerful influence in this study. Willingness to work decreased if respondents lacked a personal family pandemic flu plan, if they weren't confident that their employer would ensure their family's safety while they cared for patients with pandemic flu, and even if vaccine and antiviral medication were provided for both nurse and family.…”
Section: Discussionsupporting
confidence: 52%
“…5 Previous studies have found HCWs’ PPE usage, including respiratory protection, to be at suboptimal levels. 710 Common documented gaps in practice include improper use of respirators (eg, incorrect donning or doffing procedures) and failure to correctly use recommended types of respiratory protection. 11–14 …”
mentioning
confidence: 99%
“…Among these factors were listed nurses' insufficient theoretical and clinical knowledge of appropriate nursing practices during a pandemic, the fear of contracting the disease or infecting family members, and the concern of work overload during an outbreak as well as the need to work for additional hours (Cheong et al, 2007;Daugherty, Perl, Rubinson, Bilderback, & Rand, 2009;Ehrenstein, Hanses, & Salzberger, 2006;Martin, 2011;Qureshi et al, 2005;Wong et al, 2010;Yonge, Rosychuk, Bailey, Lake, & Marrie, 2007).…”
mentioning
confidence: 99%